2020
DOI: 10.3390/s20113283
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Single-Value Indicators for Centrifugal Pump Based on Vibration Signals

Abstract: Off-design operation conditions might not only seriously affect the internal flow status of a centrifugal pump, but also result in additional energy loss and potential mechanical damage. Therefore, early-stage monitoring and predication on off-design operation conditions for centrifugal pumps have become essential. Single-value indicators have favorable factors such as a smaller amount of calculation and easier identification. As a result, industries prefer the more straightforward approach: obtaining single-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The main challenge in this application is extracting features from the vibration signals that can accurately represent the faults for effective fault detection. One limitation is that fault signatures are often feeble signals, masked by heavy background noise [ 9 ]. Most of the time, feature extraction methods require complex preprocessing to improve the signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge in this application is extracting features from the vibration signals that can accurately represent the faults for effective fault detection. One limitation is that fault signatures are often feeble signals, masked by heavy background noise [ 9 ]. Most of the time, feature extraction methods require complex preprocessing to improve the signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Using online monitoring of the centrifugal pump flow, pressure, head, and other performance parameters, Liu et al identified the four states of cavitation, loosening, rotor misalignment, and rotor unbalance according to threshold comparison method. Luo et al [5] established the relationship between characteristics and state by analyzing the time domain and frequency domain characteristics of the vibration signal of the centrifugal pump. Cao et al [6] extracted 15 characteristic indexes of the vibration acceleration signal of the centrifugal pump, established the relationship between cavitation and characteristic indexes, and realized cavitation state monitoring of the centrifugal pump according to the characteristics of the vibration signal.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal pumps are widely used in construction, municipal water supply and drainage, petroleum and chemical industries, thermal power and other industries [1,2]. Most pumps are driven by motors and their electricity consumption is huge [3,4]. Due to the high energy consumption of centrifugal pumps, the frequency conversion technology has been widely adopted to adjust the speed of centrifugal pump by means of a frequency converter, thus plays an important role in energy saving in the pump industry [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several neural networks and data-driven empirical models (also named as soft sensors/analyzers) have been developed alternatively in the fluid machinery field [1,2,4,[19][20][21][22][23][24][25][26][27]. Compared with mechanism models, the process data can reflect the characteristics without a sufficient understanding of the mechanism.…”
Section: Introductionmentioning
confidence: 99%